"Blockchain and Land Administration" - Makala, Baloko; Anand, Aanchal (UNOPS, 2019)
Blockchain is the technology that powers the much-talked about cryptocurrency, Bitcoin. However, Bitcoin is just one application of the blockchain. Blockchain is essentially a “chain of blocks,” where each block represents a set of records. Each such record could, in turn, represent a cryptocurrency, a land plot, a diamond, or even an identity. In this sense, if the traditional Internet is an Internet of information, blockchain is considered the “Internet of value.” Therefore, the technology has the potential to revolutionize the way value is stored and exchanged.